Cathode Stability Provided by New Electrolyte containing Cyano‐benzimidazole‐based Lithium Salt: Insights From In Situ DRIFTS Analysis. Issue 1 (3rd November 2016) - Teshager, Minbale Admas; Hwang, Bing‐Joe; Chern, Yaw‐Terng; Lin, Shawn D.
Abstract: New electrolytes with good thermal and electrochemical stabilities can improve lithium‐ion batteries for applications at high temperatures and high‐potential working conditions. In this study, the solid–electrolyte interphase (SEI) formed in the presence of the new 5‐cyano‐bis(trifluoroborane)‐trifluoromethyl‐benzimidazole lithium salt is examined on two cathodes, that is, commercial LiCoO2 and Li‐rich Li1.2 Ni0.2 Mn0.6 O2 cathodes, using in situ diffuse reflectance infrared Fourier‐transform spectroscopy (DRIFTS). The SEI species contain no decomposition products related to the new electrolyte, up to a potential of 5.0 V. During the first charging process, SEI formation starts at an onset potential of 4.4 or 4.5 V for LiCoO2 or Li1.2 Ni0.2 Mn0.6 O2, respectively, which is higher than that observed by using commercial LiPF6 electrolyte. SEI species of acid anhydride, alkyl carbonates, and Li2 CO3 are identified at and beyond the onset potential, which can be attributed to the decomposition of organic carbonates. Furthermore, SEI formation is relatively insignificant in the second‐cycle charging, indicating the formation of a passivating layer in the first cycle, in contrast to the continuing SEI formation through cycling with LiPF6 electrolyte. The different SEI formed with the new electrolyte can be attributed to the adsorption of the electrolyte anion on the electrode surface. This study demonstrates changes in SEI formation chemistry with the new electrolyte, which appears to be a suitable candidate for transition‐metal‐oxide cathodes at high voltage conditions. Abstract : In situ DRIFTS : A new cyano‐benzimidazole‐based lithium salt can provide good cathode stability. The lithium salt shows no sign of decomposition up to 5.0 V and the onset potential of solid–electrolyte interphase formation shifts to higher potentials than observed when using LiPF6 in the same solvent. The improved stability is attributed to the interaction between the new electrolyte and the cathode surface.